2019
DOI: 10.1002/etc.4381
|View full text |Cite
|
Sign up to set email alerts
|

Amitriptyline at an Environmentally Relevant Concentration Alters the Profile of Metabolites Beyond Monoamines in Gilt‐Head Bream

Abstract: The antidepressant amitriptyline is a widely used selective serotonin reuptake inhibitor that is found in the aquatic environment. The present study investigates alterations in the brain and the liver metabolome of gilt‐head bream (Sparus aurata) after exposure at an environmentally relevant concentration (0.2 µg/L) of amitriptyline for 7 d. Analysis of variance–simultaneous component analysis is used to identify metabolites that distinguish exposed from control animals. Overall, alterations in lipid metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 65 publications
1
9
0
1
Order By: Relevance
“…The PLS-DA model clearly differentiates the two conditions and this fact is confirmed through the corrected t-test for multiple comparisons that showed that the levels of the first two metabolites in the VIP plot (i.e., tryptophan and creatinine) are significantly (q-value = 0.081) lower in C14 (Table SI.7). The time-dependent effect was also observed in other exposure experiment set-ups carried out with fish (Ziarrusta et al, 2019), probably due to the different number of fish present in the tank along the experiment. In this case, since glass eels are fasting, we could think that the metabolism might show a kind of depletion effect in some of the metabolites.…”
Section: Analysis Of the Polar Metabolomesupporting
confidence: 52%
See 2 more Smart Citations
“…The PLS-DA model clearly differentiates the two conditions and this fact is confirmed through the corrected t-test for multiple comparisons that showed that the levels of the first two metabolites in the VIP plot (i.e., tryptophan and creatinine) are significantly (q-value = 0.081) lower in C14 (Table SI.7). The time-dependent effect was also observed in other exposure experiment set-ups carried out with fish (Ziarrusta et al, 2019), probably due to the different number of fish present in the tank along the experiment. In this case, since glass eels are fasting, we could think that the metabolism might show a kind of depletion effect in some of the metabolites.…”
Section: Analysis Of the Polar Metabolomesupporting
confidence: 52%
“…Metabolomics is often used in toxicology to find the biochemical pathways disturbed by a stressing event (e.g., disease, nutritional imbalance, contaminant exposure…), because the search of altered small endogenous metabolites (<1.5 kDa) can provide a clear insight into the health status of an organism. In fact, environmentalmetabolomics has been successfully applied to explore the cause-effect mechanisms of CECs in aquatic organisms (Colás-Ruiz et al, 2022;Labine et al, 2022;Xu et al, 2022;Ziarrusta et al, 2019) and it is one of the key elements in adverse outcome pathways (Brockmeier et al, 2017;Dumas et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the studied cohorts were large enough, that work opened the possibility to broaden the scope and to address a more in-depth study based on non-targeted analysis to find key biomarkers beyond the ones determined through target analysis approach. For this reason, we have implemented a metabolomic approach to study the lipidic phase isolated in the previous work by means of high performance liquid chromatography coupled to high resolution mass spectrometry (HPLC-HRMS), as it has been carried out previously 23,24 . This way, a better understanding of the relation between cannabis abuse and SZ development would be achieved and potential biomarkers could be suggested.…”
Section: Introductionmentioning
confidence: 99%
“…Adibidez, uretatik bertan dauden animalietara, elikadura-kate trofikoetan hedatzen direlarik [2]. Plentziako Itsas Estazioan urraburuekin egindako esposizio-esperimentuak frogatzen du amitriptilina (antidepresiboa), ziprofloxazinoa (antibiotikoa) eta oxibentzona (ultramore-iragazkia) arrainetan biometatzen direla, eta, horrez gain, kutsatzaile horiek arrainen plasman, burmuinean eta gibelean albo-ondorioak eragiten dituztela [7].…”
unclassified